Winter days in the Big Woods adapted from the Little house books by Laura Ingalls Wilder - Wilder, Laura Ingalls 1867-1957; Graef, Renaee (My first Little house books, 1994)
A little pioneer girl and her family spend the winter in their log cabin in the Big Woods of Wisconsin.